Mutual Investments Funds in Shares in Brazil : Incentives, Management and Convergence - Paulo Rogério Faustino Matos; Christiano Modesto Penna; Ana Balbina Gomes Silva (BBR: Brazilian Business Review)
This article analy zes patterns of convergence in series of return of investment funds in shares in Brazil, from the use of the methodology of Phillips and Sul (2007). Unlike the theory of portfolios and in disagreement with the characteristics of this market -regulation, t ransparency, efficiency and informational transaction costs-, it shows a heterogeneous behavior, from the formation of four clubs with specific transition and composition dynamics. The private nature of the management legal entity, the incentives associat ed with the recovery of low administrative fees, in addition to rates of performance and the emphasis on gains offset by risks, differentiate funds that are losers or winners.